Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
Step-by-step explanation:
Can you help me with this please
-42=5(2c+9)-3(c+8)
-42 - 7c + 21 = 0
c = -(-63)/-7
c = -9
[tex]-42 = 5(2c+9)-3(c+8)\\\\\implies -42 = 10c + 45 -3c - 24\\\\\implies 7c = -42 -45 +24 \\\\\implies 7c = -63\\\\\implies c = -\dfrac{63}7 = -9[/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.